Memory Impairment Allied to Temporal Lobe Epilepsy and its Deterioration by Phenytoin: A Highlight on Ameliorative Effects of Levetiracetam in Mouse Model - Mohan, Asher John; Krishna, Kamsagara Linganna (International Journal of Epilepsy, 2018)
Background/Objectives Memory impairment (MI) and epilepsy go hand in hand, mainly in conditions of temporal lobe epilepsy (TLE). This disease comorbidity has been reported to worsen upon treatment. Hence this study aims to evaluate the extent of aggravating effect of phenytoin (PHT) at normal and reduced doses on MI associated with TLE and additionally assesses the protective effect of levetiracetam (LEV) on these adverse effects.Methods Swiss albino mice of either sex (n = 36) were used for this study in which seizures were induced by intraperitoneal administration of pilocarpine (300 mg/kg i.p.) followed by evaluation of antiepileptic activity by technique of Racine's scale for convulsive scores. Errors (a factor denoting MI) were assessed using radial arm maze. Finally brain biochemical measures of acetylcholinesterase and glutamate along with cresyl violet staining and estimation of total neuronal number of the hippocampus were performed.Results Exacerbation of MI by PHT was observed, where the extent of MI was found to be lesser in the reduced dose approach (PHTR: 28.50 ± 1.03; p ≤ 0.05). However, this tactic in dose reduction was interfered with the antiepileptic potential of the drug. Attenuation of MI upon combining with LEV, without an interference in the principal treatment, was observed equally in the behavioral and brain aspects of the study (PHTN + LEV: 1.33 ± 0.33 and PHTR + LEV: 1.00 ± 0.17; p ≤ 0.05).Conclusions The promising effects of LEV could thus aid in proposing a new management remedy for TLE to minimize the adverse effect associated with it.
Keywords: pilocarpine; phenytoin; levetiracetam; antiepileptic drugs